2014
DOI: 10.1073/pnas.1413169111
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic HIV-1 RNA is mainly transported by diffusion in the presence or absence of Gag protein

Abstract: Significance HIV-1 full-length RNA must go to specific subcellular compartments to carry out its functions as a template for translation of structural and enzymatic proteins and as the genetic material for new virions. RNA mislocalization can affect the functions of the RNA and its encoded proteins, causing defects in viral replication. Currently, little is known about how HIV-1 RNA is transported in the cytoplasm. Here, we demonstrate that HIV-1 full-length RNAs use diffusion as the major mechanism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
76
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(91 citation statements)
references
References 46 publications
(57 reference statements)
14
76
0
Order By: Relevance
“…It is possible that once the viral RNA leaves the TIRF observation volume, it rarely or never reenters this region; in this scenario, the length of time an RNA molecule can be tracked, i.e., ϳ3 s, is the amount of time the RNA stays near this region. However, we observed that most HIV-1 RNAs move in a nondirectional, random-walking manner in the cytoplasm (27). Thus, it is highly likely that a large portion of the RNAs may leave and reenter the region near the plasma membrane; in this scenario, the time that the RNAs stay near the plasma membrane may be longer than indicated by the track lengths of the viral RNAs.…”
mentioning
confidence: 79%
See 4 more Smart Citations
“…It is possible that once the viral RNA leaves the TIRF observation volume, it rarely or never reenters this region; in this scenario, the length of time an RNA molecule can be tracked, i.e., ϳ3 s, is the amount of time the RNA stays near this region. However, we observed that most HIV-1 RNAs move in a nondirectional, random-walking manner in the cytoplasm (27). Thus, it is highly likely that a large portion of the RNAs may leave and reenter the region near the plasma membrane; in this scenario, the time that the RNAs stay near the plasma membrane may be longer than indicated by the track lengths of the viral RNAs.…”
mentioning
confidence: 79%
“…Construct 1-GagBFP-BSL was derived from 1-GagCeFP-BSL (3) by replacing the cerulean fluorescent protein (CeFP) gene with the blue fluorescent protein (BFP) gene (29). Constructs 1-Gag⌬CTDBFP-BSL and 1-Gag⌬CTD-BSL were derived from 1-GagBFP-BSL and 1-Gag-BSL (27), respectively, by deleting the region encoding the last 83 amino acids of the capsid. Plasmid 1-GagLZCeFP-BSL was constructed by replacing a portion of the gag sequence of 1-GagCeFP-BSL (3) with the counterpart from 1-GagLZmCherry-BSL (27), which encodes a leucine zipper motif in place of the NC domain.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations